Lyophilization of Nanocapsules: Instability Sources, Formulation and Process Parameters - Ghania Degobert; Dunya Aydin (MDPI AG, 2021)
Polymeric nanocapsules have gained more and more interest in the medical sciences. Their core-shell structure offers numerous advantages, especially regarding their use as drug delivery systems. This review begins by presenting the different intrinsic sources of the instability of nanocapsules. The physical and chemical potential instabilities of nanocapsules reduce their shelf-life and constitute a barrier to their clinical use and to their commercialization. To overcome these issues, lyophilization is often used as a process of choice in the pharmaceutical industry especially when labile compounds are used. The state of the art of lyophilization nanocapsules is reviewed. The formulation properties and the process parameters are discussed for a complete understanding of their impact on the stability and storage of the final dried product. To assess the quality of the dried product, various characterization methods are also discussed.